Understudied social influences on work-related and parental burnout: Social media-related emotions, comparisons, and the “do it all discrepancy” - Black, Kristen Jennings; Cunningham, Christopher J. L.; Gillespie, Darria Long; Wyatt, Kara D. (Frontiers in Psychology, 2022)
Recent societal changes, including a global pandemic, have exacerbated experiences of and attention to burnout related to work and parenting. In the present study, we investigated how several social forces can act as demands and resources to impact work-related and parental burnout. We tested two primary hypotheses in a sample of women who responded to an online survey (N for analyses ranged from 2376 to 3525). We found that social comparisons, social media use, negative emotions when comparing oneself to others on social media, and a high do it all discrepancy (feeling one should be able to do it all more so than perceptions that one can) were correlated with higher reports of work-related and parental burnout. Alternatively, positive emotions when comparing oneself to others and social support were related to lower reports of work-related and parental burnout. The influence of social media use on burnout was mediated by the emotions experienced when comparing oneself to others on social media. Tests of moderation indicated that social comparisons had stronger relationships with burnout for those with higher expectations that they should be able to do it all verses can do it all. Tests of social support as a moderator of the relationships between social demands and burnout were largely non-significant. Based on these findings, we make practical suggestions for interventions to increase positive emotions experienced from social media use, and to mediate the do it all discrepancy by redefining expectations around “doing it all”.